Molecular Consequences of the Myopathy-Related D286G Mutation on Actin Function - Fan, Jun; Chan, Chun; McNamara, Elyshia L.; Nowak, Kristen J.; Iwamoto, Hiroyuki; Ochala, Julien (Frontiers in Physiology, 2018)
Myopathies are notably associated with mutations in genes encoding proteins known to be essential for the force production of skeletal muscle fibers, such as skeletal alpha-actin. The exact molecular mechanisms by which these specific defects induce myopathic phenotypes remain unclear. Hence, in the present study, to better understand actin dysfunction, we conducted a molecular dynamic simulation together with ex vivo experiments of the specific muscle disease-causing actin mutation, D286G located in the actin-actin interface. Our computational study showed that D286G impairs the flexural rigidity of actin filaments. However, upon activation, D286G did not have any direct consequences on actin filament extension. Hence, D286G may alter the structure of actin filaments but, when expressed together with normal actin molecules, it may only have minor effects on the ex vivo mechanics of actin filaments upon skeletal muscle fiber contraction.